Smart inertial sensor-based navigation system for flexible snake robot - Billah, Md. Masum; Khan, Md. Raisuddin (2014)
The position and orientation of a robot during the navigation is a big challenge to the researchers. The received signal strength information (RSSI) of Wifi or Bluetooth or RFID is the available way to solve this issue for the localization researches. But the obstacles in the environment are very big challenge for this technology. RSSI should be vulnerable depends on the obstacle, if it is dynamic environment then there is nothing to say about this signal. Thus inertial sensors like accelerometer and rate gyro are chosen for flexible snake robot localization in planar surface navigation. This paper describes the methods of navigation positioning system using inertial sensor and finally, perform the experiment with the flexible snake robot for indoor position and orientation.